Measuring Time and Risk Preferences: Realiability, Stability, Domain Specificity - Eva Wölbert; Arno Riedl (Center for Economic Studies and ifo Institute (CESifo), 2013)
To accurately predict behavior economists need reliable measures of individual time preferences and attitudes toward risk and typically need to assume stability of these characteristics over time and across decision domains. We test the reliability of two choice tasks for eliciting discount rates, risk aversion, and probability weighting and assess the stability of these characteristics over time and across situations. We find high reliability and that individual characteristics are remarkably stable over time. The estimated parameters correlate well with self-reported decisions in financial domains, but are largely uncorrelated with decisions in other important life domains involving intertemporal trade-offs and risk.
Keywords: C18; C91; D03; D80; D90; 330; time discounting; risk aversion; probability weighting; reliability; stability; domain specificity; experiment